On the design of stabilising fiscal rules - Wolf Heinrich Reuter; Oļegs Tkačevs; Kārlis Vilerts (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2018)
Utilising data of the EU28 Member States for the period 1996-2015, this paper confirms the findings of previous studies that the stipulation of fiscal rules reduces fiscal volatility and consequently contributes to macroeconomic stability. Yet, we document that this result only holds for rules which are designed to be unaffected by the current state of the business cycle, i.e. which are "a-cyclical". Those can, e.g. be budget balance rules that set ceilings in cyclically adjusted terms or expenditure rules that set a limit relative to potential instead of current output. Furthermore, the stringency of fiscal rules amplifies their stabilising effect. Actual year-to-year compliance with fiscal rules seems to play no systematic role, such that effects of the rules can be observed even if they are not complied with year-to-year. Overall, our paper suggests that strong, properly designed numerical rules act as an anchor for fiscal policy makers and contribute to more stable discretionary fiscal policy.
Keywords: C23; E62; E32; H60; 330; fiscal rules; fiscal policy volatility; panel data; compliance